1981
DOI: 10.1136/jnnp.44.2.148
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phenytoin on phenobarbitone and primidone metabolism.

Abstract: SUMMARY Serum concentrations of primidone and its metabolites-phenobarbitone and phenylethylmalonamide-were measured in 40 epileptic patients receiving treatment with primidone alone or primidone plus phenytoin. Serum phenobarbitone concentrations were also measured in 100 patients receiving phenobarbitone, alone or with phenytoin. Patients receiving either phenobarbitone or primidone in combination with phenytoin showed raised serum phenobarbitone concentrations. Phenytoin also caused raised phenylethylmalona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In particular, concurrent administration of PHT was associated with a modest decrease in PB CL/F, which reached statistical significance within the elderly group. A decrease in PB CL/F by PHT is consistent with results of previous studies, in which PHT was found to increase serum PB concentration, presumably by inhibiting PB metabolism (23,24). In our study, CBZ also appeared to have a modest lowering effect on PB CL/F, although again this reached statistical significance only in the elderly population.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, concurrent administration of PHT was associated with a modest decrease in PB CL/F, which reached statistical significance within the elderly group. A decrease in PB CL/F by PHT is consistent with results of previous studies, in which PHT was found to increase serum PB concentration, presumably by inhibiting PB metabolism (23,24). In our study, CBZ also appeared to have a modest lowering effect on PB CL/F, although again this reached statistical significance only in the elderly population.…”
Section: Discussionsupporting
confidence: 92%
“…Phenobarbital concentrations have been reported to increase upon introduction of phenytoin comedication (Lambie & Johnson 1981;Morselli et a1. 1971).…”
Section: Phenytoinmentioning
confidence: 99%